PARENT'S KNOWLEDGE REGARDING INFLUENZA DISEASE AND VACCINE IN INDONESIA - Dwi Endarti; Viva Starlista; Tri Murti Andayani (Universitas Muhammadiyah Magelang, 2020)
Influenza vaccine is a vaccine that is not included in the national immunization program. An approach to support decision making for the introduction of influenza vaccine into national immunization programs by conducting a survey knowledge of parents in Indonesia that influences decision making for vaccinations. The purpose of this study was to determine the level of parental knowledge about influenza and influenza vaccines and to know the factors that influence. The research design used is observasional with a multi-center cross-sectional approach. The research instrument used a questionnaire to determine sociodemographic characteristics and level of knowledge. Data was collected through a survey of 500 parents respondents in 5 provinces in Indonesia, namely in West Java, DIY, Lampung, Central Sulawesi and Central Kalimantan using convenience sampling techniques. Data were analyzed using the Mann Whitney test. Resul of the study showed the average knowledge of respondents related to influenza disease and vaccine was 78.55±12.43. Only 145 (29%) parents know that influenza vaccines are not included in Indonesia's national immunization program. There was a significant difference in the value of knowledge between groups of characteristics in the experience of hearing influenza vaccine (p = 0,000) and the source of disease information (p = 0.045). It is recommended for government and health workers to carry out educational programs related to influenza and influenza vaccines to achieve equitable distribution of information and increase public knowledge.